1996
DOI: 10.1073/pnas.93.15.8005
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic feedforward projections from the inferior colliculus to the medial geniculate body.

Abstract: A novel and robust projection from y-aminobutyric acid-containing (GABAergic) inferior colliculus neurons to the medial geniculate body (MGB) was discovered in the cat using axoplasmic transport methods combined with immunocytochemistry. This input travels with the classical inferior colliculus projection to the MGB, and it is a direct ascending GABAergic pathway to the sensory thalamus that may be inhibitory. This bilateral projection constitutes 10-30% of the neurons in the auditory tectothalamic system. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
112
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 36 publications
11
112
0
Order By: Relevance
“…Preliminary studies suggest a possible phylogenetic difference and lack of VGLUT1 expression in MGBv of adult primate (Ito and Takada, 2011). The latter may be related to other phylogenetic differences including higher concentrations of inhibitory interneurons in MGBv (Winer et al, 1996;Peruzzi et al, 1997) and higher resolution of frequency responses to sound in cats and primates versus rats (Schreiner et al, 2000;Cheung et al, 2001;Read et al, 2002;Polley et al, 2007). These and many other factors likely contribute to variation in vesicular transporter gene and protein expression patterns during development as well as across species.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies suggest a possible phylogenetic difference and lack of VGLUT1 expression in MGBv of adult primate (Ito and Takada, 2011). The latter may be related to other phylogenetic differences including higher concentrations of inhibitory interneurons in MGBv (Winer et al, 1996;Peruzzi et al, 1997) and higher resolution of frequency responses to sound in cats and primates versus rats (Schreiner et al, 2000;Cheung et al, 2001;Read et al, 2002;Polley et al, 2007). These and many other factors likely contribute to variation in vesicular transporter gene and protein expression patterns during development as well as across species.…”
Section: Discussionmentioning
confidence: 99%
“…None of the cases produced any significant trends (P≫0.05) for latency shifts as a function of stimulation location. For more details on the analysis method, see Results: "Latency versus location" 2005) and/or within the medial geniculate nucleus (Winer et al 1996;Peruzzi et al 1997;Bartlett et al 2000;Ito et al 2009;Lee and Sherman 2010) that may not sufficiently respond to the artificially synchronized activation of groups of neurons induced by electrical stimulation. There is some evidence in the cat that greater inhibitory patterns are observed in caudal ICC regions compared to more rostral regions in response to ipsilateral pure tone stimulation based on 2-deoxyglucose mapping (Webster et al 1984).…”
Section: Possible Mechanisms For the Caudal-rostral Effectsmentioning
confidence: 99%
“…Animal studies have demonstrated that projections from the IC to the medial geniculate nucleus are both excitatory and inhibitory (Winer et al 1996;Peruzzi et al 1997;Bartlett et al 2000). Furthermore, the largest tectothalamic neurons are inhibitory (i.e., GABAergic), represent up to 45% (in rat; 20% in cat) of the ascending projections, and provide fast transmission to the medial geniculate nucleus that can precede the excitatory tectothalamic input (Winer et al 1996;Peruzzi et al 1997;Ito et al 2009).…”
Section: Possible Mechanisms For the Caudal-rostral Effectsmentioning
confidence: 99%
“…Anatomical studies suggest that the inhibitory feedforward projections to the MGB arise throughout the IC (9,10), and physiological investigations find several distinct classes of excitatory and inhibitory inputs (11)(12)(13). However, the topographic organization of excitatory and inhibitory inputs in the tectothalamic pathways is largely undefined.…”
mentioning
confidence: 99%